Lithium-ion battery anode materials based on silicate-containing spherical natural graphite

Through temperature treatment and carbon-based coating technology on natural graphite, the problem of difficulty in removing silicon-based impurities in natural graphite is solved, and a high-performance and low-cost lithium-ion battery negative electrode material is produced.

JP7621337B2Active Publication Date: 2025-01-24SYRAH RESOURCES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022511261
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-21
Filing Date
2020-08-21
Publication Date
2025-01-24
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

In the prior art, when producing lithium-ion battery negative electrode materials, it is difficult to efficiently, safely and economically remove silicon-based impurities, especially silicate minerals, in natural graphite, resulting in a degradation of battery performance.

Method used

The temperature treatment method is adopted and combined with carbon-based coating technology, natural graphite is treated by pyrolysis and carbonization to form a carbonized coating, avoiding the use of dangerous hydrofluoric acid treatment, reducing the treatment temperature and reducing environmental pollution.

Benefits of technology

It realizes efficient and safe production of carbon anode materials, maintains or improves the electrochemical performance of lithium-ion batteries, and reduces production costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621337000005
    Figure 0007621337000005
  • Figure 0007621337000006
    Figure 0007621337000006
  • Figure 0007621337000007
    Figure 0007621337000007
Patent Text Reader

Abstract

Materials and novel methods for producing carbon anodes for Li-ion batteries are described. These materials use natural flake graphite that has been processed to improve physical properties, but retains residual impurities, including silicates and other silicon-containing minerals, that are economically difficult to remove. For the purposes of producing battery anode materials, further purification is required, traditionally using hydrofluoric acid, which requires significant additional costs and environmental controls. The alternative novel process is a lower cost and more environmentally friendly alternative compared to standard acid refining using hydrofluoric acid. Methods are provided for the direct graphitization of unpurified spheroidized graphite materials containing carbonaceous coatings in the manufacture of lithium-ion battery anodes. Materials produced using these methods include synthetic graphite and particulate silicon or SiO. x It may be mixed with materials to enhance their properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a provisional application entitled "Lithium-ion battery anode material based on spherical natural graphite," assigned No. 62 / 889,816, filed on August 21, 2019, the entire contents of which are incorporated herein by reference.

[0002] In particular, the present disclosure is directed to methods for treating natural graphite that may be advantageously utilized to manufacture carbon anodes for Li-ion batteries. The present disclosure is also directed to treated natural graphite that is particularly useful in the manufacture of carbon anodes for Li-ion batteries.

[0003] In an exemplary embodiment of the present disclosure, a method is provided for direct graphitization of spheroidized graphite material including a carbonaceous coating in the manufacture of Li-ion battery anodes. The disclosed direct graphitization method may be entirely temperature based, i.e., may eliminate chemical refining steps entirely, or may include a chemical refining step that eliminates hydrofluoric (HF) acid treatment, to produce a material suitable for the manufacture of Li-ion battery anodes.

[0004] In a further exemplary embodiment of the present disclosure, natural graphite is processed to upgrade its grade, but retains residual silicon-based impurities, including silicates and other silicon-containing minerals that are difficult to eliminate from an economic standpoint. The processed material produced using the disclosed method can be synthetic graphite and / or particulate silicon and / or silicon oxide (SiO x ) materials to improve performance. [Background technology]

[0005] Natural graphite has traditionally been used as an anode material for Li-ion batteries due to its ability to intercalate into lithium. Natural graphite is popular due to its low cost compared to artificially produced graphite, such as graphite produced from calcined coke. Currently, natural graphite ores are mined using both open-cut and underground mining. Graphite-bearing ores are processed through a series of mechanical treatments that liberate the graphite minerals from the host rock by crushing, grinding, screening, flotation, and drying, and refine the screened minerals into a concentrated bulk product.

[0006] The natural graphite mineral concentrates obtained from these processes yield a range of flake products differentiated based on size and purity. Subsequent classification separates the concentrate into flake size distribution categories that correspond to specific applications. Physical beneficiation processes such as flotation are typically capable of achieving purity levels reaching about 94%-98% total carbon (TC) content.

[0007] The impurities in the concentrate are naturally occurring minerals that are consistent with the graphitic host rock, also known as gangue minerals. Gangue minerals are typically free from the graphite in the concentrate, but may also be attached to or embedded within the graphite flakes. The majority of gangue minerals in graphite concentrate are silicates or other silicon-containing minerals, including quartz, feldspar, and layered silicates. Graphite concentrate also contains sufficient amounts of aluminum and iron oxides, as well as other contaminants that are undesirable / harmful in anodes for lithium-ion battery applications.

[0008] More generally, heterogeneous and uncontrolled mixtures in lithium-ion batteries have a high risk of generating side reactions that reduce the performance and reliability of the battery. As a result of natural processes and formation, impurities may or may not be homogeneous, presenting a control risk that can be mitigated by refining carbon materials, such as graphite, to the highest commercially viable level. To control impurities, the battery anode material industry has established chemical and thermal refining processes to remove impurities and achieve very low ash levels (TC >99.9%, preferably TC >99.98%).

[0009] For lithium-ion battery applications, natural graphite concentrates must undergo various additional processing steps to meet the stringent requirements adopted by the industry. Specifically, flake graphite is processed to obtain very specific physical and chemical properties in terms of size, density, morphology, high purity and surface treatment. This processing typically involves mechanical crushing and shaping of graphite particles, followed by a refining process, usually a chemical refining process, via a process called spheroidization. For the production of precursors for lithium-ion battery anode active materials, natural graphite with a smaller flake size distribution, typically in the range of 60 μm-150 μm (d50), is used as feed material. Additional size reduction of the graphite by grinding is usually required to meet the requirements of a specific powder form for the end use.

[0010] In thermal refining (i.e. non-chemical refining), the heat treatment must be carried out at a temperature sufficient to vaporize / sublimate the impurities. In particular, the removal of silicate-based minerals requires very high temperatures in the range corresponding to the graphitization temperatures applied in the production of artificial graphite. This process can be dangerous, energy / time consuming and therefore costly. Thermal refining also requires furnace systems capable of removing and managing the gases released from the graphite particles during the various stages of the heat treatment.

[0011] Chemical refining, on the other hand, can be done by both alkaline and acid treatments to leach residual minerals from the graphite. Acid treatment is more common and typically uses a mixture of hydrochloric (HCL), sulfuric (H2SO4) and hydrofluoric (HF) acids. After chemical refining, the product is washed to remove residual acids and salts.

[0012] After chemical or thermal refining, graphite typically contains greater than 99.90% carbon.

[0013] The mineralization that is most difficult to remove is generally based on elemental silicon, the most prominent form of this impurity being silicates. Thermal refining is most problematic due to the presence of silicon carbide, which is formed as a by-product of the decomposition of silicon oxide and the subsequent reaction of silicon with carbon. Silicon carbide is a stable compound that does not sublime below temperatures of 2600°C to 2800°C. Chemical refining processes preferably use hydrofluoric acid, as it is an efficient way of dissolving the silicon-containing minerals from the graphite. Unfortunately, chemical refining processes using HF are associated with environmental, health and safety concerns, necessitating environmental controls. Summary of the Invention [Problem to be solved by the invention]

[0014] Despite previous efforts, there remains a need for materials / methods that allow for the production of highly efficient carbon anode materials from natural graphite in a cost-effective, safe and efficient manner. These and other beneficial objectives are achieved by the materials and methods disclosed herein. [Means for solving the problem]

[0015] The present disclosure provides an advantageous method for treating natural graphite, which may be utilized, inter alia, to produce carbon anodes for Li-ion batteries. The present disclosure further provides a treated natural graphite material, particularly useful for producing carbon anodes for Li-ion batteries. Natural graphite may be treated to upgrade or to retain residual silicon-based impurities, including silicates and other silicon-containing minerals, that are economically difficult to remove. The treated material may or may not be spheroidized. The treated material may be coated with a carbonaceous material (e.g., pitch) and subjected to a temperature-based treatment to obtain a carbonized or graphitized surface layer. Such treatments, including temperature treatments, may purify the graphite particles to greater than 99.95% carbon by weight. The treated material produced using the disclosed methods may be modified with synthetic graphite and / or particulate silicon and / or SiO to improve performance. x It may be mixed with the material.

[0016] In accordance with the present disclosure, a process is disclosed whereby spheroidized natural graphite and carbonaceous material (e.g., pitch) are subjected to only a temperature-based process, i.e., no acid treatment, to achieve cost-effective, environmentally friendly, direct graphitization of the carbonaceous material as a coating and refinement of the core graphite particles. In another embodiment, chemical treatment of the graphite may be performed prior to the graphite / carbonaceous material combination in conjunction with the temperature-based process. However, in accordance with the present disclosure, the chemical treatment associated with this alternative embodiment does not include treatment of the graphite with HF, thus eliminating the most expensive and potentially hazardous form of chemical treatment associated with conventional operations. The process temperature for graphitization of the disclosed graphite / carbonaceous material may be lower than previously considered feasible for graphitization of carbonaceous materials. This lower temperature is made possible based on the recognition that silicon-based impurities do not need to be removed to produce a graphite-based precursor material that can be effectively utilized in lithium-ion battery anode fabrication.

[0017] The disclosed graphite treatment methods and treated graphite materials produced according to the present disclosure exhibit important advantages, such as lower cost and more environmentally friendly performance compared to traditional acid purification methods (e.g., using hydrofluoric acid) and high temperature purification techniques, without sacrificing anode functionality in lithium ion battery applications using the treated materials produced thereby.

[0018] In an exemplary embodiment of the present disclosure, a precursor material for use as a lithium-ion battery anode is provided. The precursor material is made from natural graphite, i.e., graphite material in its mined natural form. The precursor material is processed to retain its metal-based and non-metal-based impurities. In a further exemplary embodiment of the present disclosure, the precursor material may be processed to contain / retain silicon-based minerals at levels of 0.5 to 2 wt.% silicon, while such processing is effective to substantially remove native metal-containing compounds, such as compounds containing iron, aluminum, sodium, calcium, manganese, magnesium, vanadium, and / or titanium (such as silicates, oxides, clays, sulfides, etc.), to levels of less than 0.05 wt.%. Silicon-based minerals may be present / retained in the precursor material in various forms, for example, as silicate(s) and / or silicon carbide-based mineral(s).

[0019] The disclosed precursor materials may be used to produce lithium ion battery anode materials via direct pyrolysis, carbonization and / or graphitization processes in which carbonaceous materials coat graphite precursor particles. The lithium ion battery anode materials thus produced may contain / retain native silicon material after post-processing or may be partially or fully purified to predetermined specifications.

[0020] When using natural graphite as a lithium ion battery anode material, the natural graphite is typically treated to form a carbonized or graphitized carbonaceous coating to obtain better performance characteristics. The resulting coated natural graphite particles are shown diagrammatically in FIG. 1. In particular, FIG. 1 diagrammatically illustrates a carbonaceous coated natural graphite particle. A spheroidized natural graphite core (A) is coated with a carbonaceous material and heat treated to a carbonization or graphitization temperature to form a carbonized or graphitized coating (B). In an exemplary embodiment of the present disclosure, the inner core (A) is natural graphite and the outer coating (B) is a carbonaceous material. The natural graphite inner core (A) may retain natural metallic and non-metallic impurities or may retain natural silicon (at least about 0.5 wt. % silicon) while being substantially free of other non-metallic and metallic impurities. The carbonaceous coating material is preferably treated with SiO 2 prior to forming the carbonaceous coating (B). x and / or may be mixed with a silicon precursor.

[0021] In an exemplary embodiment of the present disclosure, the lithium ion battery anode material produced from the disclosed precursor material (i.e., having residual silicon-based minerals) may be coated with a pyrolyzed, carbonized, and / or graphitized pitch material or a polymeric material. Chemical vapor deposition (CVD) methods may also be utilized as known in the art. The pitch material used to coat the lithium ion battery anode material may have a softening point at a temperature of about 200° C. to 300° C., but may also have a softening point below 200° C. The polymeric material may be, for example, an epoxy resin, a phenolic resin, polyacrylonitrile, polyvinyl alcohol, or polystyrene. An exemplary polymeric coating is described in CN100420627C to Morgan Hairong, the disclosure of which is incorporated herein by reference. In an exemplary embodiment, the pitch is a SiO x and / or may be mixed with a silicon precursor, thereby introducing additional silicon-based materials into the lithium-ion battery anode.

[0022] Thus, the lithium ion battery anode material may be treated by heat treatment at a carbonization temperature, for example, a temperature between 900°C and 1900°C, preferably between 1050°C and 1400°C.

[0023] Additionally, the lithium ion battery anode material may be further processed by heat treating at a graphitization temperature between 2200°C and 3000°C, preferably between 2400°C and 2900°C.

[0024] The disclosed lithium ion battery anode material may be mixed with synthetic graphite, which is typically done separately from and subsequent to the heat treatment step described above.

[0025] In an exemplary embodiment, the lithium ion battery anode is mixed with synthetic graphite, the ratio of synthetic graphite to precursor material typically ranging from 20 / 80 to 80 / 20 (synthetic graphite / precursor material).

[0026] The lithium ion battery anode material disclosed herein may be prepared by adding SiO x and / or may be mixed with other silicon-based material(s) to achieve the desired silicon level in the final anode member.

[0027] The disclosed lithium ion battery anode materials may be further processed to obtain desired properties. For example, the lithium ion battery anode materials may be further processed using spheronization and grinding techniques to enable a predetermined material capacity measured in mAh / g. In an exemplary embodiment, the lithium ion battery anode materials are further processed to provide a material capacity of greater than 372×(1−((N / 100) / 0.467)), where N is the relative percentage amount of silicon in the anode (based on the precursor material). As noted above, the amount of silicon retained in the precursor material may range from 0.5-2 wt % while still achieving effective anode function in lithium ion battery applications.

[0028] Additional features, functions and advantages of the disclosed methods and materials will become apparent from the following detailed description. [Brief description of the drawings]

[0029] To assist one of ordinary skill in the art in making and using the disclosed invention, reference is made to the accompanying figures. [Figure 1] FIG. 1 shows a schematic diagram of natural graphite coated with a carbonaceous material. [Diagram 2] FIG. 2 shows the capacity data for the refined natural graphite material. [Diagram 3] FIG. 3 shows an SEM image of the refined natural graphite material. [Figure 4] FIG. 4 shows three flow charts: FIG. 4A shows a method for in situ refining and graphitizing pitch-coated natural graphite in accordance with the present disclosure, eliminating chemical refining process steps; FIG. 4B shows a method for refining and graphitizing pitch-coated natural graphite in accordance with the present disclosure, reducing chemical refining steps and eliminating the use of HF acid; FIG. 4C shows a comparison / exemplary method including chemical refining. [Diagram 5] FIG. 5 shows the first cycle efficiency (%) and capacity data for the graphitized material using chemically refined and unrefined precursors. [Figure 6] FIG. 6 shows a comparison of metal impurity reduction with different processing temperatures. [Figure 7] FIG. 7 shows a comparison of the electrochemical properties of materials processed at different temperatures. [Figure 8] FIG. 8 shows the relative anode material costs on a weight and energy basis as a function of residual SiO2 content. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] As discussed above, the present disclosure provides an advantageous method for treating natural graphite that can be used to manufacture carbon anodes for Li-ion batteries. The disclosed treatment methods are effective in producing graphite characterized by enhanced quality, which may be further characterized by the retention of silicon-based impurities, including silicates and other silicon-containing minerals, at levels that exceed silicon impurity levels previously considered acceptable in the industry. The treated graphite material of the present disclosure may be produced in a more cost-effective and environmentally acceptable manner compared to prior art processing processes, yet still provide effective functionality for lithium-ion battery applications. In fact, the disclosed treatment methods may utilize only temperature-based processing, i.e., no acid treatment, in the manufacture of lithium-ion battery anodes in a cost-effective and environmentally friendly manner. The treated graphite material produced using the disclosed methods may be produced using synthetic graphite and / or particulate silicon and / or SiO x It may also be mixed with materials to enhance properties.The following description serves to further explain and demonstrate advantages associated with the disclosed methods and materials.

[0031] Figure 2 shows the specific charge capacity data for several natural graphite (NG) materials that have been processed by standard commercial methods for producing battery anode materials, including chemical purification processes. The physical appearance of these natural graphite materials is demonstrated by SEM analysis and is shown in Figure 3.

[0032] Specific charge capacity is an important characteristic for battery performance and is used to qualify materials that exhibit acceptable performance. For natural graphite battery anode materials, specific charge capacity is expected to be in the range of 350 mAh / g to 370 mAh / g, preferably greater than 360 mAh / g. This charge capacity measurement represents the ability of the natural graphite material to intercalate lithium ions when used as a battery anode material. Graphite materials may be modified to improve other required performance, including first cycle efficiency, power capability, and endurance capability. These modifications may involve tradeoffs with the inherent charge capacity of the material.

[0033] To achieve such improvements, in a common type of natural graphite battery anode material, after spheroidization and purification, the spherical or spheroidized natural graphite may be coated with coal tar pitch or petroleum tar pitch or other carbonaceous material and heat treated to form a carbonized surface that coats the individual graphite particles. In this specification, the terms "spheroidized" and "spheroidized" are synonymous and are used interchangeably. The purpose of this coating is to improve the performance characteristics of the natural graphite when used as a battery anode material, particularly by forming a physical barrier between the spherical graphite particles and the electrolyte liquid in the completed battery. To balance the specific capacity and performance characteristics of the coated particles, the coating should be as thin as practical while maintaining a homogeneous specific surface coverage within the desired thickness range. In one such process, the spherical natural graphite is coated with petroleum tar pitch or coal tar pitch. In such a coating process, about 0.5 to 10 wt. % pitch may be used.

[0034] In one such process, the coating may be performed by mechanically mixing and distributing finely ground pitch evenly on the surface of the spheroidal graphite so that a homogenous coating is obtained during heat treatment of the material in a dedicated furnace. The pitch-coated graphite is heated to form a carbonized coating after undergoing physical pyrolysis and carbonization. The heat treatment may be performed in the range of 1050°C to 1400°C to form a carbonized coating, or in the range of 2200°C to 3000°C to both form a carbonized coating and graphitize the formed carbonized coating. The resulting carbon-coated or graphitized carbon-coated natural graphite material is supplied as a product for use as an anode material in lithium-ion batteries.

[0035] Examples of conventional processes typical for the natural graphite lithium ion anode industry, as discussed above, can be found in patents CN100338802C and CN200410027615X to BTR, US 6,403,259 to Kitagawa et al. (Mitsubishi Electric Industry Co., Ltd. / Mitsubishi Chemical Co., Ltd.), and CN100420627C to Morgan Hilong.

[0036] In one exemplary embodiment of the present disclosure, a petroleum tar pitch or coal tar pitch coating with a softening point in the range of 60° C. to 320° C., preferably 200° C. to 300° C., is combined with a naturally occurring / natural graphite material at a graphite to pitch ratio of 0.5% to 10.0%, more preferably 3% to 6%, by mass equivalent. The pitch coating is further converted to a carbonized coating by stepwise heat treatment at a maximum temperature not exceeding 1800° C., more preferably below 1650° C., or alternatively, converted to a graphitized coating by high temperature heat treatment at a temperature of 2200° C. to 3000° C., more preferably at a temperature of 2400° C. to 2900° C.

[0037] Multiple experiments were conducted using unrefined and refined graphite materials from the same deposit and processing plant, which demonstrated advantageous processing routes and processed materials that are particularly useful for producing anode materials for use in lithium-ion batteries. In particular, it was found that by using low purity graphite as a precursor in the disclosed heat treatment process, a significantly lower cost anode material product can be produced as compared to conventional graphite materials that meet industry-based purity standards.

[0038] In an exemplary embodiment, the processing of naturally occurring / natural graphite material according to the present disclosure into a material usable as an anode material for lithium-ion batteries comprises a process that includes: (i) a heat treatment to remove naturally occurring impurities, typically carried out at a temperature range of 1500° C. to 3000° C.; or (ii) a chemical refining step using an acid, but specifically excluding HF; or (iii) a combination of said heat treatment and chemical refining processes (excluding HF-based chemical refining).

[0039] Example 1 As an example of the present disclosure, the present specification provides an advantageous process for direct graphitization as shown in Figure 4A (Process 1). In Process 1, natural flake graphite, which is mined and beneficiated through a series of beneficiation steps, is dried and classified before being transferred to a crushing and molding process. The powder is then coated and subjected to a single heat treatment purification step that combines pyrolysis, carbonization and graphitization. The coated graphite is subjected to a graphitization temperature, such as between 2200°C and 3000°C, to purify the graphite particles and graphitize the coating layer.

[0040] In accordance with the present disclosure, it has been determined that by higher temperature thermal processes (i.e., temperatures above 2850°C), silicon-based impurities and other metal-based impurities can be completely removed by sublimation from the purified / graphitized material without destroying the new graphitized carbon coating (artificial graphite coating from pitch) on the graphite particles. Notably, the resulting carbon-coated graphitized spheroidal graphite material exhibited high electrical capacitance consistent with the natural graphite precursor material.

[0041] Additionally, a comparison of several different processed materials with and without the initial metal-based impurities in the feedstock showed similar mechanical and electrochemical properties. This result demonstrates that in certain graphite applications, pre-purification of the uncoated spheroidal natural graphite or pitch-coated natural graphite materials prior to graphitization of the coating layer is not necessary. This result further demonstrates that pre-carbonization of the pitch coating prior to graphitization of the coating layer is not necessary.

[0042] In the following, an example implementation of process 1 of FIG. 4A according to the present disclosure is described.

[0043] The feedstock is standard grade flake graphite with a purity of greater than 95% total carbon (TC) as measured by loss on ignition (LOI) method. The particle size specification of standard grade flake graphite is greater than 80% passing through a 100 mesh screen and less than 25% passing through a 325 mesh screen using standard laboratory screening methods. A spheroidization process is introduced by combining grinding, forming and selective classification of unrefined flake graphite. In this spheroidization process, the flakes are first ground in one or more air classifiers or faculty mills in series to reduce the material to an initial target particle size distribution before forming. The sized material is then fed to one or more air classifiers or faculty mills in series to form ellipsoidal or spherical particles. The material is classified at each stage of grinding to remove by-product fines. The process continues until the final target particle size distribution, shape and tapped bulk density are obtained. Such intermediate products are defined in this specification as "unrefined, uncoated spheroidal graphite."

[0044] The coating process follows, in which finely ground pitch solids, preferably having a size range between 2 and 10 microns, are combined with the unrefined spheroidal graphite. Other coating methods commonly used in the industry, including solvent-based and vapor deposition methods, may also be employed. Mechanical mixing of the two components produces a coating layer of pitch material secured around the surface of the unrefined spheroidal graphite particles. The pitch used as the coating is a mixture of either coal tar pitch or petroleum tar pitch, or both, and preferably has a softening point in the range of 200°C to 300°C, although pitches with lower softening points (e.g., softening points below 200°C) may also be used.

[0045] The coated unrefined spheroidal graphite may be processed in a continuous powder-based graphitization process. However, in an exemplary embodiment, the coated unrefined spheroidal graphite is loaded into a crucible or boat and fed into a graphitization furnace. The furnace may be a stationary furnace with heating and cooling cycle control, or the material may be transported or conveyed through various heating and cooling zones to achieve the desired thermal profile in a continuous process. Alternatively, a rotary furnace or other continuous furnace may be used.

[0046] Heating the coated graphite in an inert atmosphere, such as argon or nitrogen, at a temperature range of 300°C to 600°C decomposes the organic compounds in the pitch and releases volatile components. Continued heating at temperatures above 1050°C converts the pitch completely to carbon, forming a carbonized coating layer around the spherical graphite particles. Continued heating in the range of 2400°C to 2600°C gradually converts the carbonized coating layer and the non-graphitized components in the initial material to graphitic molecular structures. Further heating from 2400°C to above 2600°C to above 2900°C results in the gradual reduction of oxide-based metal impurities in the graphite to carbides and ultimately sublimation or vaporization, further refining the graphite. The cooled and screened product can then be used in lithium-ion battery anodes.

[0047] FIG. 5 shows the materials and electrochemical properties tested in Process 1 and compares them to materials produced from purified precursors, i.e., precursors processed to meet industry requirements for impurity levels. Both unpurified and chemically refined 16 μm spherical natural graphite precursors were coated with 3% and 6% pitch-to-graphite by weight, respectively. The coated samples were graphitized at 2900° C. for 4 hours in a heating step. The capacity and coulombic efficiency of the resulting graphitized samples were determined using coin cell tests. The results showed that the unpurified coated samples, after the subsequent heat treatment process, performed similarly to the purified coated samples in the key battery performance indicators of first cycle efficiency (FCE) and capacity.

[0048] Table 1 (below) shows the graphite crystal basal plane interlayer spacing d for the samples provided by Process 1. 002 and the degree of graphitization are similar to the results obtained for the sample provided by Process 3 (control) shown in FIG. 4C, indicating graphitization of the purified coating precursor. [Table 1]

[0049] Based on the above, it is apparent that precursor materials processed according to Process 1 - which substantially removes (e.g., to levels of less than 0.05 wt.%) metal-based impurities, such as mixtures containing iron, aluminum, sodium, calcium, manganese, magnesium, vanadium, and / or titanium - exhibit substantially equivalent performance for lithium-ion battery applications. It is apparent that Process 1 provides a more cost-effective and environmentally acceptable method for producing precursors compared to Process 3 for lithium-ion battery applications.

[0050] Additional testing was conducted according to Process 1, whereby unrefined natural spheroidal graphite was coated with petroleum-based tar pitch and heat treated at three different temperatures, 2400°C, 2600°C, and 2900°C, and the products were analyzed by X-ray fluorescence spectroscopy (XRF). Figure 6 compares the iron, aluminum, and silicon compositions of the materials treated at different temperatures with those of the uncoated and coated precursor materials. The compositions demonstrate that heat treatment reduces impurities in all samples, with the higher treatment temperatures of 2600°C and 2900°C providing greater impurity reduction.

[0051] Materials produced from the 2600°C and 2900°C processes were electrochemically tested to determine charge capacity and first cycle efficiency. FIG. 7 shows a comparison of the electrochemical properties with two commercially available natural spheroidal graphite anode materials. The first comparative material is a chemically refined, pitch-coated, carbonized natural spheroidal graphite. The second comparative material is a pitch-coated, carbonized, graphitized natural spheroidal graphite. The comparison of the electrochemical properties demonstrates that the charge capacity and first cycle efficiency of the material processed according to Process 1 are equal to or better than the commercially available products, and that the retention of at least some of the aluminum, iron, and silicon impurities has a negligible effect on the charge capacity or first cycle efficiency.

[0052] Example 2 In a second embodiment of the present disclosure, a graphite material is used as an anode material in a lithium ion battery and is made in whole or in part from a naturally occurring graphite material containing naturally occurring silicon-based impurities, and the treatment of the naturally occurring or native graphite material is effective to reduce the silicon content in the graphite material used to make the anode material to a range of 0.5% to 5% (by weight) elemental silicon.

[0053] Of note, the processing of naturally occurring / natural graphite to form the desired precursor is selected to allow for the retention of silicon minerals while substantially removing other metal-based and non-metal-based impurities, such as compounds (silicates, oxides, clays, sulfides, etc.) containing iron, aluminum, sodium, calcium, manganese, magnesium, vanadium, and / or titanium. In particular, metal impurities (other than silicon) are reduced in accordance with the present disclosure to levels typically below 0.05% by weight (elemental metal basis) each, while silicon-based minerals are maintained within the indicated ranges (i.e., 0.5 to 5% by weight elemental silicon). Materials produced using such cost-optimized processing methods have been found to have substantially equivalent charge capacities on a relative graphite mass basis after correcting for the silicon-based minerals present in the precursor.

[0054] It is anticipated that some of the silicon-based contamination of the graphitic material retained in the precursor according to the present disclosure will be chemically and electrophysically inactivated in a lithium-ion battery when subjected to standard battery operating conditions, i.e., operation in conventional state of charge (SOC) ranges and conventional voltage ranges. As long as metal-containing compounds such as compounds containing iron, manganese, and other metal-containing compounds that are soluble in lithium-ion battery applications are removed and dendrite formation is avoided, a low-cost anode material with similar energy capacity as standard refined materials can be produced.

[0055] By leaving the silicon-based mineral contamination (at levels described herein) but removing the transition metals, chemical refining can be sufficiently reduced or eliminated to produce an alternative, low-cost anode material with residual silicon-based contamination that exhibits electrochemical properties currently acceptable for lithium-ion battery applications. Thus, the present disclosure identifies processing regimes for producing precursors that exhibit comparable functionality for lithium-ion battery anode applications while being cheaper and more environmentally friendly. The ability to reduce the refining of naturally occurring / natural graphite without sacrificing precursor functionality is unexpected and directly contradicts long-standing industry thinking regarding the purity characteristics required for precursor materials for use in the manufacture of anodes for lithium-ion batteries.

[0056] Table 2 shows the impurity levels as measured by XRF for unrefined spherical natural graphite material from various sources. Source A has a silicate content ranging from 3.15% to 3.75%, Source B has a silicate content ranging from 1.52% to 1.97%, Source C has a silicate content of 1.67%, Source D has a silicate content of 1.56%, Source E has a silicate content of 3.2%, and Source F has a silicate content of 1.5%. The silicate content is expressed as both weight percent SiO2 equivalent, which is the assumed chemical form of silicate, and as weight percent elemental silicon. The iron content, expressed as weight percent Fe2O3 equivalent, ranges from 0.3% to 0.48% for samples from all sources. [Table 2]

[0057] Table 3 shows the specific capacity data for two spheroidized graphite samples, each tested before and after conventional refining. The refined natural graphite - i.e., natural graphite processed according to conventional spheroidization and refining techniques to reduce silicon impurities below conventional industry standards - demonstrates a measured specific capacity approaching the theoretically expected value of 372 mAh / g for natural graphite. For the unrefined / natural sample, the presence of impurities (including especially silicon-based impurities) reduces the specific capacity of the material as less active graphite contributes to the measured specific capacity. However, the material demonstrates a capacity (typically greater than 330 mAh / g) that is in the practical range useful for lithium-ion battery applications. [Table 3]

[0058] In accordance with the present disclosure, the process allows silicon-containing minerals to be retained through the refining process, reducing processing costs and eliminating the need for HF in the acid wash process, thereby also reducing the environmental impact of the refining process. This fundamental improvement to the process allows for a lower cost option, presenting an approach that is particularly well suited for highly cost-sensitive lithium-ion battery applications.

[0059] In accordance with the present disclosure, it is believed that a combination of physical processing techniques with high temperature treatments can be used to produce natural graphite containing silicon-based impurities that exhibit higher than expected specific charge capacity. High temperature treatments remove impurities, and it is known that silicon-based impurities usually require the highest temperatures to sublimate. Typically, silicon-based impurities are first converted to silicon carbide (SiC). Somewhat differently than silicates (e.g., SiO2), silicon carbide can be incorporated into the graphite structure and inhibit electrochemical intercalation (charging) or intercalation (discharging). Thus, the presence of silicon carbide can reduce the capacity of lithium-ion batteries.

[0060] In accordance with the present disclosure, physical powder processing techniques, including spheronization and sizing, are used to refine the natural graphite particle structure into a size and shape suitable for use as a lithium-ion battery anode material. This physical powder processing typically alters the surface properties of graphite and may overcome the inhibiting features of SiC, thereby enabling higher than expected capacity. Notably, the processing process relies on physical processing but does not include costly / environmentally unfriendly processing steps aimed at removing silicon-based impurities, providing reduced processing costs based at least in part on the elimination of processing operations aimed at reducing / removing silicon levels to meet industry standards for silicon levels for lithium-ion battery applications.

[0061] Typically, the expected capacity of natural graphite would be 372 mAh / g, assuming 100% graphite. Impurities (such as silicon in the form of silicates) are inert and reduce the capacity of a lithium-ion battery in proportion to their mass percentage. Since it is assumed that the majority of silicon-based impurities are in the form of silicates (chemical structure SiO2), knowing the level of silicon-based impurities, the expected capacity can be calculated by the following formula:

[0062]

number

[0063] It is unexpected to produce a higher capacity in a lithium-ion battery than predicted by equation (1), and such an unexpected result would indicate that the processing technique(s) have altered the morphology of the silicon impurity such that it contributes less to passivation to the battery's capacity than predicted by equation (1).

[0064] In accordance with the present disclosure, further advantageous processing methods are provided for the production of precursors particularly useful in lithium-ion battery applications. In particular, Process 2, shown in FIG. 4B, utilizes the same feedstock as used in Process 1 (above) and includes a hydrochloric acid (HCL) purification step prior to the pitch coating step. Optionally, the final heat treatment step may operate at a lower maximum temperature, such as 1700° C. or as low as 1200° C. Chemical HCL purification removes many metallic impurities, most notably iron, but provides limited dilution of silicon-based impurities.

[0065] Unpurified spherical graphite is mixed with a partially used or fresh dilute acid solution containing hydrochloric acid. The slurry is heated to a temperature typically not exceeding 60° C. to 80° C. and mixed continuously for an extended period of time, typically 8 to 12 hours. The solids are separated from the acid mixture via a filter. The filtered solids may be further processed via subsequent dilute batches of used or fresh acid solution to improve purity.

[0066] A coating process is then utilized in which finely ground pitch solids having a size range of 2 to 10 microns are combined with partially refined graphite spheroids and the two components are mixed to coat the graphite spheroids with pitch. Other coating methods commonly used in the industry may also be implemented, including solvent-based and vapor deposition methods. The pitch used for coating is typically a coal tar pitch or petroleum tar pitch, preferably having a softening point in the range of 200°C to 300°C, although lower softening point pitch materials may also be used. Mixtures of low and high softening point pitches may also be used.

[0067] The coated graphite spheroids are loaded into crucibles or boats and transferred to a graphitization furnace. As mentioned above, a continuous power-based graphitization process may be utilized. The graphitization furnace may be a stationary furnace with controlled heating and cooling cycles, or the material may be transferred or conveyed through various heating and cooling zones to obtain the desired thermal profile. Alternatively, a rotary furnace or other continuous furnace may be used. Initial heating of the coated, partially purified graphite spheroids occurs at temperatures ranging from 300°C to 600°C, where the organic compounds in the pitch are decomposed by pyrolysis and volatile components are released. Continued heating to 1200°C is then applied, where the pitch is completely reduced to carbon, forming a carbonized coating around the graphite spheroids. This product is referred to as the "Process 2a Product" and may be used selectively as the final product. The powder may then be further heat treated, ideally in the range of about 2200°C to 3000°C, to gradually convert the carbonized coating and non-graphitized carbon components in the initial material to graphite, and, if necessary, reduce residual impurities to desired levels. This product, also referred to as the "Process 2b Product", may be used as the final product.

[0068] The products from Process 1 (FIG. 4A), Process 2a (FIG. 4B), and Process 2b (FIG. 4B) may be mixed with synthetic graphite powders characterized by similar size regimes. Synthetic graphite of smaller particle size may also be used. Such synthetic graphite powders are well known in the industry and are usually produced from pitch precursors. Synthetic graphite typically has a smaller capacity than natural graphite, but has the advantage of a longer cycle life. Natural graphite generally has the advantage of a higher capacity and lower cost. Thus, the innovative materials as produced by Process 1, Process 2a, and Process 2b and the mixtures of these products with synthetic graphite have the advantages of low cost, high capacity, and long cycle life when used in batteries.

[0069] Example 3 In yet another blended product, active silicon is further blended into the product to increase capacity. Such silicon can be pure fine silicon particle powder or SiO 2 , as described in the patent literature (see, for example, JP2005149946, CN102394287B, US5624606 and JP2000-203818A). x Silicon may be added at a level of about 1 to about 15% by weight relative to the graphite, and such silicon addition may be in the range of about 5 to 10% by weight of graphite to added silicon. All of the products described in Process 1, Process 2a, and Process 2b, or combinations thereof with synthetic graphite, may contain Si or SiO x Exemplary silicon powders that may be used in combination with the graphite described herein include the silicon materials described in US 9,614,216 (Hitachi Chemical) and CN103022435 (Shanshan Technology).

[0070] Furthermore, SiO x Or when mixed with silicon, such powders may be mixed with the pitch during the pitch coating process, and the silicon remains in the pitch-coated areas of the natural graphite powder when produced according to Process 1, Process 2a, and Process 2b.

[0071] Such silicon and SiO x The mixture may be used to increase the capacity of the anode material beyond the theoretical capacity of 372 mAh / g for the pure graphite material. For precursor materials with inert silicon, the total silicon will be higher than for the pure material mixed with only silicon.

[0072] Figure 8 shows the relative cost of pitch coated carbonized spheroidal natural graphite versus %SiO2 content. Theoretical calculations of the impact of residual silicate content on the cost of carbon coated anode material are presented here. The major parameters that affect the processing cost according to conventional graphite processing are (i) reagent cost (e.g., HF), (ii) labor cost, and (iii) energy cost. According to the present disclosure, the reagent cost and chemical processing process cost are significantly reduced or completely eliminated, thereby substantially reducing the overall cost of graphite processing for lithium ion battery applications while providing effective / acceptable charge capacity performance.

[0073] For the purpose of the cost / performance analysis, the specific capacity of the carbon-coated refined natural graphite is 370 mAh / g. By fixing the cost of chemical refining of the spheroidal graphite precursor, the material and energy costs of anode materials made from various contents of residual silicate in the precursor were calculated. Figure 8 shows the relative material and energy costs versus the amount of residual silicate represented by the Si weight content in the pitch-coated carbonized spheroidal natural graphite, based on the material cost ($ / kg) and energy cost ($ / Wh) of the anode material made from the chemically refined precursor. Typically, the higher the amount of residual silicon, the lower the material and energy costs. However, when the amount of residual Si is greater than 1.3 wt%, the cost reduction effect diminishes and starts to negatively impact the cost per energy due to the inert mass of the material represented by the Si material. Thus, an optimal range of Si content is identified for the benefit of the cost per unit energy while also obtaining the benefit of the cost reduction per unit weight compared to the complete removal of the Si impurity.

[0074] Although the present disclosure has been described with reference to exemplary embodiments / examples, the present disclosure is not intended to be limited by or to such exemplary descriptions.

Claims

1. 1. A method for heat treatment of a coated graphite material, comprising: a. combining a natural graphite material with a carbonaceous material; b. subjecting the combination of natural graphite material and carbonaceous material to a temperature treatment step effective to increase the graphite purity and to effect pyrolysis, carbonization and / or graphitization of the carbonaceous material; Equipped with This produces coated graphite that is useful for use as a lithium ion battery anode material; The temperature treatment step preserves silicon-based impurities in the natural graphite at a level of at least 0.5% silicon by weight. method.

2. 10. The method of claim 1, wherein the carbonaceous material comprises at least one of a petroleum tar pitch, a coal tar pitch, a polymeric material, a hydrocarbon liquid, and a hydrocarbon gas.

3. 3. The method of claim 2, wherein the carbonaceous material is a polymeric material selected from the group consisting of epoxy resins, phenolic resins, polyacrylonitrile, polyvinyl alcohol, and polystyrene.

4. The method of claim 1 , wherein the temperature treating step comprises direct graphitization of the coated graphite.

5. The method of claim 1, further comprising mixing the temperature treated coated graphite with at least one of synthetic graphite, SiO x or a silicon precursor.

6. The method of claim 1, wherein the natural graphite material is not subjected to an acid treatment process.

7. The method of claim 1, wherein the natural graphite material is subjected to an acid treatment process, the acid treatment process not including treatment with HF.

8. A lithium ion battery anode material comprising graphite containing at least 0.5 wt.% residual silicon, the residual silicon being retained by natural graphite.

9. A lithium ion battery anode material comprising graphite containing at least 0.5% by weight residual silicon, the graphite being combined with a carbonaceous material that has been carbonized or graphitized to form a carbonaceous coating, the residual silicon being retained by the natural graphite.

10. The lithium ion battery anode material of claim 9, wherein the carbonaceous material comprises at least one of petroleum tar pitch, coal tar pitch, and a polymeric material.

11. The lithium ion battery anode material of claim 10, wherein the carbonaceous material is a polymeric material selected from the group consisting of epoxy resins, phenolic resins, polyacrylonitrile, polyvinyl alcohol and polystyrene.

12. The lithium ion battery anode material of claim 9, wherein the carbonaceous material has a softening point between 200°C and 300°C.

13. The lithium ion battery anode material of claim 9, wherein the carbonaceous material has a softening point of less than 200°C.

14. The lithium ion battery anode material of claim 9, wherein the graphite or coated graphite is mixed with synthetic graphite to form a mixed lithium ion battery anode material.

15. The lithium ion battery anode material of claim 14, wherein the ratio of synthetic graphite to graphite or coated graphite is within the range of 20 / 80 and 80 / 20.

16. The lithium ion battery anode material of claim 9, wherein the graphite or coated graphite is mixed with SiOx and / or one or more silicon-based materials.

17. A method for producing a lithium ion battery anode precursor material, comprising subjecting a natural graphite material, retaining at least 0.5% silicon by weight, to a temperature treatment step, without a preceding chemical refining step, to increase the graphite purity to a level effective for use as a lithium ion battery anode material.

18. The method of claim 17, wherein the natural graphite contains 0.5 to 2.0 weight percent silicon.

19. The method of claim 17, wherein the temperature treatment step is effective to substantially remove metallic impurities other than silicon-containing impurities.

20. The method of claim 17, wherein the temperature treatment step is effective to substantially remove Fe, Al, Na, Ca, Mn, Mg and V admixtures, as appropriate.

21. The method of claim 17, wherein metal impurities other than silicon-containing impurities are removed to a level of less than 0.05 weight percent.

Citation Information

Patent Citations

  • Anode material for lithium-ion secondary battery, its manufacturing method and battery using this

    JP2004179015A

  • COMPOSITE GRAPHITE PARTICLE, ITS PRODUCTION METHOD, Li ION SECONDARY BATTERY CATHODE MATERIAL, Li ION SECONDARY BATTERY CATHODE AND Li ION SECONDARY BATTERY

    JP2004210634A

  • Compound graphite and lithium secondary cell using same

    JP2007141677A

  • Composite carbon cathode material for lithium ion battery and method for producing the same

    JP2008542981A

  • Nonaqueous electrolytic solution and nonaqueous electrolyte secondary battery using the same

    JP2017152241A